Changes in total carotenoid content at different stages of traditional processing of yellowfleshed cassava genotypes - Maziya-Dixon, B.B.; Dixon, Alfred G.O.; Ssemakula, G.N. (Wiley, 2009)
The changes in content of total carotenoid at each stage of processing cassava storage roots were investigatedwith three improved yellow-fleshed cassava varieties (TMS 94⁄0006, TMS 01⁄1235 and TMS 01⁄1371)grown in 2005⁄2006 in a randomised complete block design with two replications at Ibadan, Nigeria. Whenthe cassava roots were grated to a mash, results obtained indicate that there was a significant reduction intotal carotenoid content for all the genotypes. The reduction was highest for TMS 01⁄1235 (1.20lgg)1),intermediate for TMS 01⁄1371 (0.78lgg)1) and least for TMS 94⁄0006 (0.35lgg)1). In most cases, weobserved higher total carotenoid concentration, especially when the intermediate step involved pressing toremove excess water, and during roasting compared with the initial concentration in the raw cassava storageroots. In conclusion, grating, drying and cooking to a paste resulted in reduction of total carotenoid content,while roasting and pressing resulted in higher carotenoid concentration. A change in total carotenoid contentduring processing depends on variety, processing method, especially unit operation and the initial totalcarotenoid content of the variety.